As possibilidades de uso de ferramentas da informática: software para análise de dados qualitativos e ISD - Ferreira, Anise A. G. [UNESP] (Editora Unisinos, 2007)
The objective of the present article is to identify and discuss the possibilities of using qualitative data analysis software in the framework of procedures proposed by SDI (socio-discursive interactionism), emphasizing free distribuited software or free versions of commercial software. A literature review of software for qualitative data analysis in the area of social sciences and humanities, focusing on language studies is presented. Some tools, such as: Wef-tQDA, MLCT, Yoshikoder and Tropes are examined with their respective features and functions. The software called Tropes is examined in more detail because of its particular relation with language and semantic analysis, as well as its embeded classification of linguistic elements such as, types of verbs, adjectives, modalizations, etc. Although trying to completely automate an SDI based analysis is not feasible, the programs appear to be powerful helpers in analyzing specific questions. Still, it seems important to be familiar with software options and use different applications in order to obtain a more diversified vision of the data. It is up to the researcher to be critical of the analysis provided by the machine.
Applications of IT tools: software for qualitative data analysis and SDI
Keywords: qualitative data analysis; software; text analysis; discourse analysis; sociodiscursive interactionism; CAQDA